2002
DOI: 10.1037/0022-0663.94.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Assessing students' metacognitive awareness of reading strategies.

Abstract: This article describes the development and validation of a new self-report instrument, the Metacognitive Awareness of Reading Strategies Inventory, which is designed to assess adolescent and adult readers' metacognitive awareness and perceived use of reading strategies while reading academic or schoolrelated materials. There were 3 strategy subscales or factors: Global Reading Strategies, Problem-Solving Strategies, and Support Reading Strategies. The reliability and factorial validity of the scale were demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
764
4
80

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 734 publications
(1,054 citation statements)
references
References 19 publications
22
764
4
80
Order By: Relevance
“…Cronbach's coefficient alpha for internal consistency reliability of the three documented subscales (global, problem-solving, and support reading strategies) ranged from .89 to .93, and score reliability for the total sample was .93, indicating reliable measures of metacognitive awareness of reading strategies. A complete description of the MARSI, including its psychometric properties as well as its theoretical and research foundations, can be found in Mokhtari and Reichard (2002).…”
Section: Instrumentmentioning
confidence: 99%
See 4 more Smart Citations
“…Cronbach's coefficient alpha for internal consistency reliability of the three documented subscales (global, problem-solving, and support reading strategies) ranged from .89 to .93, and score reliability for the total sample was .93, indicating reliable measures of metacognitive awareness of reading strategies. A complete description of the MARSI, including its psychometric properties as well as its theoretical and research foundations, can be found in Mokhtari and Reichard (2002).…”
Section: Instrumentmentioning
confidence: 99%
“…We faced a number of theoretical, methodological, and practical challenges when we developed the original version of the MARSI (Mokhtari & Reichard, 2002), which took a significant amount of time (nearly three years) and a great deal of effort on the part of several individuals. We were highly cognizant of the fact that it would be idealistic, and perhaps impractical, to try to develop a clean and discrete measure of strategy use that is also reliable, valid, and contextualized.…”
Section: Issues and Primary Purpose Of The Marsimentioning
confidence: 99%
See 3 more Smart Citations